Seasonal sea level extremes in the Mediterranean Sea and at the Atlantic European coasts - M. N. Tsimplis; A. G. P. Shaw (Natural Hazards and Earth System Sciences, 2010)
Hourly sea level data from tide gauges and a barotropic model are used to explore the spatial and temporal variability of sea level extremes in the Mediterranean Sea and the Atlantic coasts of the Iberian peninsula on seasonal time scales. Significant spatial variability is identified in the observations in all seasons. The Atlantic stations show larger extreme values than the Mediterranean Sea primarily due to the tidal signal. When the tidal signal is removed most stations have maximum values of less than 90 cm occurring in winter or autumn. The maxima in spring and summer are less than 60 cm in most stations. The wind and atmospheric forcing contributes about 50 cm in the winter and between 20–40 cm in the other seasons. In the western Mediterranean the observed extreme values are less than 50 cm, except near the Strait of Gibraltar. Direct atmospheric forcing contributes significantly to sea level extremes. Maximum sea level values due to atmospheric forcing reach in some stations 45 cm during the winter. During the summer the contribution of the direct atmospheric forcing is between 10–20 cm. The Adriatic Sea shows a resonant behaviour with maximum extreme observed sea level values around 200 cm found at the northern part. Trends in the 99.9% percentiles are present in several areas, however most of them are removed when the 50% percentile is subtracted indicating that changes in the extremes are in line with mean sea level change. The North Atlantic Oscillation and the Mediterranean Oscillation Index are well correlated with the changes in the 99.9% winter values in the Atlantic, western Mediterranean and the Adriatic stations. The correlation of the NAO and the MOI indices in the Atlantic and western Mediterranean is significant in the autumn too. The correlations between the NAO and MOI index and the changes in the sea level extremes become insignificant when the 50% percentile is removed indicating again that changes in extremes have been dominated by changes in the mean sea level.